Maxillary sinuses’ height/width/depth of Brazilian subjects and influence of sex, age, skin color, and nutritional status: A CBCT study - Barros, Franciéllen de [UNESP] (2022)
The purpose of this study was to perform linear (two-dimensional) measurements of maxillary sinuses (MS) using cone-beam computed tomography (CBCT) images, analyze the influence of sex, age, skin color, and nutritional status, and verify differences between the right and left sides. The sample consisted of CBCT images of 238 living Brazilian subjects (139 women and 99 men). Linear measurements of maximal height, width, and depth of the right and left MS were performed with the DDS-Pro® 2.12.0_2021 software (DPP Systems, Czestochowa, Poland). All data were submitted to the statistical analysis to validate potential significant differences (p > 0.05) for sex and age and correlation to skin color and BMI. The TEM, rTEM, and R were used for intra- and inter-examiner assessments. There were differences between the sides, with significantly higher measurements on the right side for MS height and on the left side for width and depth. The MS width was only greater (p > 0.05) in men. Adult individuals (18 years or older) had higher MS height measurements than the other age groups. The measurements for skin color and BMI did not show significant differences, and it was impossible to confirm a relationship between the parameters measured. The measurements of MS height and width showed significant differences between the right and left sides and anatomic variability between the sexes for MS width, which can help analyze sexual dimorphism. There were also significant differences between the age groups. There was no significant difference in the measurements for skin color and nutritional status.